KEBIJAKAN POLITIK DAN ORIENTASI KEAGAMAAN DINASTI BUWAYHIYYAH DAN SALJUQ SERTA HUBUNGANNYA DENGAN KEKHALIFAHAN ‘ABBASIYYAH - Mokhammad Ainul Yaqin (stit-islamic-village, 2019)
Policy during the Adud in the past year 977 M. has managed to unite the tiny kingdoms that has emerged since the reign of the Buwayhid in Persia and Iraq. Religious orientation during the reign of Mu’iz al-Dawlah was participating by Shi’ah Zaidiyyah. Another case with the reign of the ‘Izz al-Dawlah and adud al-Dawlah participating Shi’ah Imamiyyah. While the relationship between the Buwayhid with ‘Abbasiyah dynasty is there are linkages between the two. Policy during the reign of the Seljuk dynasty is expanding its territory from Kasygar up to Yerussalem and from Constantinopel up to Kaspia ocean. Besides its religious orientation under the Seljuk dynasty is the Sunni Islam. While the relationship between the Buwayhid with Abbasiyah dynasty it is because of the factor similarity participating and relation marriage, so they have an emotional closeness and influence of Abbasid empire.